Half integer values of order-two harmonic numbers sums - Sofo, A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Half integer values of harmonic numbers and reciprocal binomial coefficients sums are investigated in this paper. Closedformrepresentations and integral expressions are developed for the infinite series.